Iron deficiency and symptoms in women aged 20–49 years and relation to upper gastrointestinal and colon cancers - Jean-Luc Szpakowski; Lue-Yen Tucker (BMJ Open Gastroenterology)
Objective Iron deficiency anaemia (IDA) in women aged 20–49 years may be caused by menses or gastrointestinal cancer. Data are sparse on the yield of endoscopy/colonoscopy in this population. Our aim was to determine the association of IDA and symptoms with cancers.Design Retrospective cohort study within Kaiser Permanente Northern California. Participants were women aged 20–49 years tested for iron stores and anaemia during 1998, 2004 and 2010 and followed for 5 years for outcomes of oesophageal, gastric and colon cancers. Symptoms from the three prior years were grouped into dysphagia, upper gastrointestinal (UGI), lower gastrointestinal (LGI), rectal bleeding and weight loss.Results Among 9783 anaemic women aged 20–49 years, there were no oesophageal, 6 gastric and 26 colon cancers. Incidences per 1000 for gastric cancer with and without iron deficiency (ID) were 0.60 (95% CI 0.23 to 1.55) and 0.63 (95% CI 0.17 to 2.31), and for colon cancer, 2.72 (95% CI 1.72 to 4.29) and 2.53 (95% CI 1.29 to 4.99). Endoscopies for UGI or dysphagia symptoms rather than bidirectional endoscopy for ID yielded more gastric cancers (n=5 and n=4, respectively) with fewer procedures (3793 instead of 6627). Colonoscopies for LGI or rectal bleed instead of for ID would detect more colon cancers (n=19 and n=18) with about 40% of the procedures (=2793/6627).Conclusions UGI and colon cancers were rare in women of menstruating age and when controlled for anaemia were as common without as with ID. Using symptoms rather than IDA as an indication for endoscopy found equal numbers of cancers with fewer procedures.